OPTIMIZING ENERGY MANAGEMENT IN MICROGRID SYSTEM USING ADAPTIVE CONTROL - Dimas Dityagraha, R.
Recently, the development of microgrid system is growing rapidly. Energy such as sun, wind, ocean, wave currents, and geothermal are alternative energy in developing Renewable Energy Sources (RES) in the microgrid system. Most commonly hybrid system in the microgrid is a combination between Photovoltaic (PV), ESS and diesel generation. Combination strategy control is needed for implementing this hybrid system. One of the main motivations using energy management in the microgrid is that they are capable of managing and coordinating diesel generations, storages, RES and loads in order to cost efficiency and optimizing RES. The system proposed for this study is consist of multi diesel generation, PV and batteries to supply load demand where diesel generations are local control operated. First, all active power measurements were carried out on the PCC bus. Adaptive MPC will calculate active power in the battery (charge/discharge) to optimized PV power supply in the system and maintain diesel generation power supply to load in a certain value as a base load. Then, optimize multi diesel generators that local control operated using economic dispatch method. Before the Adaptive MPC control strategy is carried out, it is necessary to calculate PV penetration active power in the system. In this thesis, adaptive MPC can be applied in the microgrid energy management system where diesel generation only operates in local control. Consideration of battery lifetime is also needed in energy management optimization because usage of the battery is very important with this strategy. Then, economic dispatch is suitable for optimizing multi diesel generation in this microgrid system.